A. Find the center of the circle.
Using the middle point formula we have:
C = ((x1 + x2) / 2, (y1 + y2) / 2)
Substituting values:
C = ((- 10 + 4) / 2, (-2 + 6) / 2)
C = ((- 6) / 2, (4) / 2)
C = (- 3, 2)
B. FInd the radius. If your answer is not an integer, express it in radical form
Using the formula of distance between points we have:
d = root ((x2-x1) ^ 2 + (y2-y1) ^ 2)
Substituting values:
d = root ((4 - (- 10)) ^ 2 + (6 - (- 2)) ^ 2)
d = root ((4 + 10) ^ 2 + (6 + 2) ^ 2)
d = root ((14) ^ 2 + (8) ^ 2)
d = root (260)
d = 2 * root (65)
Then, the radius of the circle is:
r = d / 2
r = (2 * root (65)) / 2
r = root (65)
C write an equation for the circle
The equation of the circle is:
(x + 3) ^ 2 + (y-2) ^ 2 = 65